Case report: Clinical efficacy of deep brain stimulation contacts corresponds to local field potential signals in a patient with obsessive-compulsive disorder - Duffy, Korrina A.; Fenstermacher, Elizabeth A.; Thompson, John A.; Tanabe, Jody; Patel, Moksha S.; Ojemann, Steven; Davis, Rachel A. (Frontiers in Psychiatry, 2023)
Introduction: Deep brain stimulation (DBS) is often effective in treating severe obsessivecompulsive disorder (OCD) when traditional therapeutic approaches have failed. However, optimizing DBS programming is a time-consuming process. Recent research in movement disorders suggests that local field potentials can dramatically speed up the process of identifying the optimal contacts for stimulation, but this has not yet been tested in a patient with OCD. Methods: In a patient with severe OCD, we first determined the optimal contact for stimulation for each hemisphere using traditional monopolar and bipolar review and then tested whether the clinically optimal contact in each hemisphere corresponded to local field potential signals. Results: Overall, we found that clinical efficacy corresponded with the contacts that showed the strongest local field potential signals across multiple frequency bands. Discussion: Our findings are the first indication that local field potentials could guide contact selection in patients with OCD. If validated in a larger sample, this methodology could decrease time to clinical benefit and improve accuracy in patients that are difficult to assess using traditional methods. Further research is needed to determine whether local field potentials could be used to guide finer resolution in programming parameters.